Need for orthodontic treatment in a sample of Ecuadorian adolescents from Cojitambo, 2017. (International Journal of Medical and Surgical Sciences, 2018)
Aim: To determine the need for orthodontic treatment in Ecuadorian adolescents aged 13 to 18 years in Cojitambo, 2017. Materials and methods: A cross-sectional and descriptive study was made including 140 adolescents aged 13 to 18 years, 50% males. For determining the prevalence of malocclusion, a visual clinical examination was performed to obtain the data required using the Dental Aesthetic Index (DAI). Results: 37.14% of the adolescents presented a minor malocclusion (without the need for treatment), 20% a definitive malocclusion (need for elective treatment), 30% a severe malocclusion (highly desirable treatment) and 12.86% a very severe malocclusion (mandatory treatment). No statistically significant differences were found by sex (p =0.53) or by age (p =0.05). Conclusion: There is a higher prevalence of adolescents who had a normal occlusion without the need of orthodontic treatment and the ones with the lowest prevalence were adolescents with very severe malocclusion that needed compulsory treatment, without differences by sex or age.